Effect of IAA and BAP on Micro Shoot Induction of Banana Shoot (Musa paradisiaca L) - Muhammad Sajali Sadat; Luthfi Aziz Siregar; Hot Setiado (Universitas Sumatera Utara, 2018)
The objective of the research was to determine the effect of the combination of IAA and BAP on the micro shoot induction of banana Kepok. The research was conducted at the Tissue Culture Laboratory, Horticultural Seed Center, Gedung Johor, Medan, North Sumatera, Indonesia, from October 2016 to January 2017. The completely randomized design was used with two factors; the first factor was IAA (1 mg/l, 2 mg/l, 3 mg/l, 4 mg/l) and the second factor was BAP (2 mg/l, 4 mg/l, 6 mg/l, 8 mg/l). The result showed that the application of IAA and BAP significantly affected the whole parameters observed. The combination of IAA and BAP significantly affected the percentage of shoot proliferated and the number of shoots. The combination of IAA and BAP (I4 B3) showed the highest shoot growth.Keywords: banana kepok, explant, IAA and BAP, shoot induction